The Effect Of Supply Chain Risk Management On Supply Chain Performance Through Supply Chain Integration And Information Quality In Paper Manufacturer - KURNIAWAN, YOHANES CHANDRA; TARIGAN, ZEPLIN JIWA HUSADA; SIAGIAN, HOTLAN (The journal of contemporary issues in business and government, 2021)
Globalization affects the changes in business in an area. China’s regulation in forbidding the import of recycled paper affects many paper manufacturers almost in the whole of South-East Asia. Paper manufacturer overgrew in East Java in 2017. As the demand grew fast, the Indonesian government revised an old regulation that limits the usage of woods in the paper industry. Because of the disruption, the government take policy the risk that the paper manufacturer’s owner must face just got bigger. This research aimed to identify how big supply chain risk management can affect supply chain performance through supply chain integration and information quality. The data was gathered from the paper manufacturing industry using a questionnaire. Thirty questionnaires were received from 40 questionnaires that were sent (response rate of 75 %.). Only a few samples were used because there were only 46 paper manufacturers categorized as the middle and large industry with a total worker of more than 100 people. Partial Least Square analyzed the hypothesis. The result indicates that supply chain risk management affects supply chain integration. Information quality doesn’t directly affect supply chain performance; supply chain risk management affects information quality; supply chain integration affects supply chain performance. The next research should use another type of industry and study the supplier- customer relationship.